2014
DOI: 10.1186/1423-0127-21-53
|View full text |Cite
|
Sign up to set email alerts
|

Hes-1 SUMOylation by protein inhibitor of activated STAT1 enhances the suppressing effect of Hes-1 on GADD45α expression to increase cell survival

Abstract: BackgroundHairy and Enhancer of split 1 (Hes-1) is a transcriptional repressor that plays an important role in neuronal differentiation and development, but post-translational modifications of Hes-1 are much less known. In the present study, we aimed to investigate whether Hes-1 could be SUMO-modified and identify the candidate SUMO acceptors on Hes-1. We also wished to examine the role of the SUMO E3 ligase protein inhibitor of activated STAT1 (PIAS1) in SUMOylation of Hes-1 and the molecular mechanism of Hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
(79 reference statements)
1
23
0
Order By: Relevance
“…Because PIAS1 was suggested to have a protective role against H 2 O 2 -induced cell death 25 and the anti-apoptotic gene Mcl-1 was shown to exert a neuroprotective effect in the brain, 13, 26 we first examined whether acute A β treatment increases the expression of PIAS1 and Mcl-1. Rats were divided to three groups and received 1% NH 4 OH (control group), A β (14  μ g) injection and sacrificed 30 min later, and A β injection (14  μ g) but killed 1 h later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because PIAS1 was suggested to have a protective role against H 2 O 2 -induced cell death 25 and the anti-apoptotic gene Mcl-1 was shown to exert a neuroprotective effect in the brain, 13, 26 we first examined whether acute A β treatment increases the expression of PIAS1 and Mcl-1. Rats were divided to three groups and received 1% NH 4 OH (control group), A β (14  μ g) injection and sacrificed 30 min later, and A β injection (14  μ g) but killed 1 h later.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the report that PIAS1 has an anti-apoptotic role. 25 But they are incongruent with the studies showing that PIAS1 is pro-apoptotic. 34, 35 One possible explanation for this discrepancy is that for the study showing an anti-apoptotic role of PIAS1, low concentration of PIAS1 plasmid DNA was transfected to HEK293T cells; however, for the studies showing a pro-apoptotic role of PIAS1, inducible PIAS1 expression was adopted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, we also observed that SENP1 mediates HES-1 deSUMOylation in endothelial cells (Online Figure VIII), based on a previous report. 34 N1ICD SUMOylation occurs in the cytosol or on the membrane, while HES-1 SUMOylation may occur in the nucleus; therefore, the synergistic modulation of SENP1 in NOTCH signaling-controlled endothelial growth is worthy of investigation. Moreover, there is little knowledge about the cooperation of SUMOylation with other post-translational modifications, such as ubiquitination and phosphorylation, to manipulate the efficiency of NOTCH signaling.…”
Section: Discussionmentioning
confidence: 99%
“…3G, we anticipated that arsenite might specifically regulate nucleolin SUMO E3 ligase expression or activity rather than affect the global SUMO activation (E1) or conjugation (E2) process. The SUMO E3 ligase, protein inhibitor of activated STAT1 (PIAS1), is reported to mediate the SUMOylation of hairy and enhancer of split 1 (Hes-1), which could transcriptionally regulate GADD45␣ expression as well as proapoptotic function (43). The role of PIAS1 in the regulation of nucleolin SUMOylation is currently under investigation in our laboratory.…”
Section: Discovery Of Nucleolinmentioning
confidence: 99%